The value of values in business purchase decisions. Issue 8 (12th May 2020) - Anwer, Ehtisham; Deshpande, Sameer; Derry, Robbin; Basil, Debra Z.
Abstract : Purpose: The purpose of this study is to develop and test a theoretical framework to examine business purchase decisions using the concept of "values" (personal values (PV), organizational values (OV) and values-congruency). Design/methodology/approach: The data for the study were collected from members of the Supply Chain Management Association of Canada. The relationships between perceived PV/OV/ values-congruency (IVs) and perceived role values played in business purchase decisions (DV) were hypothesized. Three factors, namely, humanity, bottomline and convention were identified using exploratory factor analysis. The hypotheses were tested using polynomial regression, which is a preferred method for measuring congruency or fit (Edwards, 1994). Findings: Perceived humanity (humaneness or benevolence) values of an organization were found to have a positive relationship with the perceived role that humanity and convention (risk aversion or compliance) values played in business purchase decisions. Perceived purchase function formalization within buying organizations was also found to have a positive relationship with the perceived role of humanity, bottomline and convention values played in business purchase decisions. Research limitations/implications: The study drew a relatively small convenience sample from a single industry association/country with a low response rate. It used the perceived role of values instead of behavioral intention or actual behavior to measure business purchasing behavior. McDonald and Gandz's (1991; 1993) list of values may be more suitable to measure OV than PV. The study only considered the buyer side of purchase decisions and values to have positive characteristics. Practical implications: Buying organizations may consider formalizing their purchase functions, clarifying their humaneness/benevolence and risk aversion/compliance values to their employees and vendors and incorporating them in the purchasing criteria/process. Similarly, selling organizations may benefit from considering these values of customers to position their products and services for better sales outcomes and business relationships. Originality/value: The study explores the role of values in business purchase contexts by proposing and testing a theoretical framework. The study has implications for practitioners and academics in the field and identifies several areas for future research.